Comorbidity profiles among sputum-positive tuberculosis patients in Cameroon - Magha, Chefor; Nchang, Lucy Cho; Weldeslassie, Michael; Nkimbeng, Desmond Akumtoh; Tchatat, Nancielle Mbiatong; Meriki, Henry Dilonga; Deribe, Kebede; Nietcho, Frank Noel; Foyet, Juluis Visnel; Fombad, Fanny Fri; Katcho, Tatiana Djikeussi; Cho, Jerome Fru; et al. (Frontiers in Tuberculosis, 2024)
Comorbid non-communicable diseases (NCDs) like diabetes, cardiovascular diseases (CVD), kidney diseases, and hypertension, could have implications for tuberculosis (TB) treatment management and increase the disease burden amongst active TB patients. This cross-sectional study aimed at profiling comorbidities amongst sputum-positive TB patients in the South West and Littoral regions of Cameroon and was relevant for improving disease management and public health interventions.Diabetes was defined by elevated blood glucose, body mass index and hypertension by elevated blood pressure levels (i.e., systolic ≥130mmHg or diastolic ≥80mmHg). Socio-demographic and clinical data were collected using case report forms. Descriptive analysis was performed, bivariate logistic regression analysis was computed with at least one comorbidity as the dependent variable (global model) and a multivariable logistic regression analysis was done to provide adjusted odds ratios (final model). The covariate with the highest p-value was removed until p ˂ 0.25 cut-off, using R software version 4.3.1. P-value ˂ 0.05 at 95 % confidence interval was considered statistically significant. Five hundred and forty-nine sputum-positive microscopically confirmed active TB patients were enrolled into this study. Two-thirds (65.8%) of the total patients were male. Overall, 56 sputumpositive TB patients had at least one non-communicable disease, thus a prevalence of 10.2 % (95 % CI = 7.9 -13.0). The most frequently recorded NCD was diabetes 4.4 % (95 % CI = 3.1 -6.7) followed by kidney disease 2 % (95 % CI = 1.1 -3.6), hypertension 0.9 % (95 % CI = 0.4 -2.2), and CVD 0.91 % (95 % CI = 0.4 -2.2). Three TB patients (0.6 %) had all four comorbidities examined. Age group (p < 0.001), and level of education (p = 0.049) were factors significantly associated with having at least one comorbidity. Our findings showed that diabetes was significantly the most prevalent comorbid NCD amongst sputum-positive TB patients (p < 0.001). HIV status, occupation, body mass index (BMI), and alcohol intake were not significantly associated with having at least one comorbidity.Implementing public health intervention programmes such as systematic screening of TB patients for NCDs especially diabetes is highly recommended for better control of these diseases.